Module to Support Self Care Behavior in Hypertension Patients in The Community: A Case Management Study - Annisa Firsty Nuri Prillianti (Health Gate, 2026)
Hypertension is a non-communicable disease that is a major risk factor for stroke, which remains a leading cause of morbidity and mortality. This study aims to determine the effectiveness of nursing care through the use of a stroke prevention module in strengthening self-care behaviors in hypertensive patients in the community. This case study was conducted in Tuliskriyo Village, Sanankulon District, Blitar Regency, involving four hypertensive patients. Data were collected through nursing assessment, physical examination, and vital sign measurement, followed by nursing interventions including pain management using Benson relaxation techniques and health education using a stroke prevention module based on self- care behavior this case management involved four hypertensive patients and describes observed clinical and behavioral changes after nursing interventions. The results showed that all patients experienced acute pain and knowledge deficits at baseline. After three days of intervention, there was a reduction in headache intensity, an improvement in vital signs, increased patient knowledge, and better adherence to antihypertensive medication and healthy lifestyle behaviors. The findings indicated that the application of a stroke prevention module effectively enhanced self-care behavior and supported improved clinical outcomes in hypertensive patients. This approach was used as an effective community-based nursing strategy to prevent stroke complications in patients with hypertension.